TMT cognitive and affective trust, psychological safety and corporate entrepreneurship - Acheampong, Shirley Maud; Adomako, Samuel; Tarba, Shlomo (Sage publications, 2026)
What enables top management teams (TMTs) to turn trust into entrepreneurial action? This article answers this question by proposing a novel theoretical account to explain why and when trust-based relationships within TMTs create strategic benefits. Drawing on social exchange theory, we examine a moderated-mediation model that shows how: (a) TMT psychological safety mediates the effect of TMT cognitive and affective trust on corporate entrepreneurship (CE; the why) and (b) social integration within TMTs moderates this mediated effect (the when). We tested our model through a multi-wave survey of 372 TMT members in 124 established firms in Ghana. Our findings reveal that the two distinct dimensions of trust (i.e. cognitive and affective) influence CE through TMT psychological safety. Our results also demonstrate that the mediated effects are more pronounced when TMT social integration is high rather than low. Implications of these findings for theory and practice are discussed.
Keywords: affective trust; cognitive trust; corporate entrepreneurship; Ghana, psychological safety; social integration; fi=InnoLab|en=InnoLab|